Guided Quick Labs and Academically Challenged Learners’ Predicting, Observing, and Inferring Skills - Salanatin, Martin John M. (Philippine Social Science Journal, 2020)
This quasi-experimental study aimed at determining the effects of guided quick labs and traditional science laboratory activities on academically-challenged Grade 10 learners’ predicting, observing, and inferring skills. The subjects in this study were the 60 academically-challenged Grade 10 learners of Antique National School in San Jose, Antique. The subjects were divided into two groups, the traditional and the quick labs. Pretest and post-test ware used to measure the predicting, observing, and inferring skills of the learners before and after exposure to both laboratory activities. The results showed that the predicting, observing, and inferring skills of the academically-challenged Grade 10 learners in both groups were comparable at the start of the six (6)-week intervention. After the intervention, the results revealed that both groups were still comparable. The findings proved that both types of laboratory activities have a similar effect in predicting and observing skills and is best improving the learners’ inferring skills.